Quantitative proteomics of Naja annulifera (sub-Saharan snouted cobra) venom and neutralization activities of two antivenoms in Africa - Tan, Kae Yi; Wong, Kin Ying; Tan, Nget Hong; Tan, Choo Hock (Elsevier, 2020)
Envenomation by Naja annulifera (snouted cobra), a non-spitting African cobra, can result in local tissue damage and fatal paralysis but a species-specific antivenom treatment is currently lacking. In this study, we investigated the quantitative proteome of N. annulifera venom, incorporating HPLC and LC-MS/MS to elucidate the venom toxicity. The immunoreactivities and in vivo neutralization activities of two hetero-specific antivenom products (Premium Serums Pan Africa polyvalent antivenom, PANAF and VINS African polyvalent antivenom, VAPAV) against the venom were subsequently examined. N. annulifera venom comprises 10 toxin families, with three-finger toxin (3FTx) being the most abundantly expressed (~78%). Within 3FTx, cytotoxin is the most dominant form and made up three-quarter of the venom bulk (~74%), whereas alpha-neurotoxins constitute <4% of the total venom proteins. Phospholipase A2 was undetected in the venom proteome, consistent with the unusual absence of PLA2 from the venoms of cobras in the Uraeus subgenus. In ELISA, PANAF and VAPAV showed comparable immunoreactivity toward the protein antigens of N. annulifera venom. These antivenoms, despite being raised against hetero-specific venoms, were capable of cross-neutralizing the lethal effect of N. annulifera venom in mice, with PANAF being marginally more potent. © 2020